Antiviral activity of mitoxantrone dihydrochloride against human herpes simplex virus mediated by suppression of the viral immediate early genes - Huang, Qiang (BMC Microbiol, 2019)
BACKGROUND: HSV-1 is a common pathogen that infects 50–90% of the human population worldwide. HSV-1 causes numerous infection-related diseases, some of which are severely life-threatening. There are antiviral medications with activity against HSV-1. However, with the emergence of drug-resistant mutant strains of HSV-1, there is an urgent need to develop new effective anti-HSV-1 agents. METHODS: Therefore, we screened a chemical library of approximately 1500 compounds to identify inhibitors of HSV-1-induced toxicity for further drug development. Moreover, we performed several experiments, including western blot analysis, Q-PCR analysis and luciferase activity assay, to explore the antiviral mechanism of the candidates. RESULTS: Here, we identified a small molecule, mitoxantrone dihydrochloride, with potency against HSV-1-induced toxicity. Furthermore, the viral titers and expression levels of HSV-1 viral proteins were potently reduced by the presence of MD in many cell lines. Using Q-PCR analysis, we found that MD efficiently reduced the transcription of viral genes that are essential for DNA synthesis, namely, UL5, UL9, UL29, UL30, UL42 and UL52. Notably, MD also significantly inhibited the transcription of the immediate early genes ICP0, ICP22, ICP27 and ICP47, all of which are required for the expression of early and late viral gene products. Using immunofluorescence and western blot analysis, we found that the antiviral effect of MD was independent of the activation of the NF-κB and MAPK pathways. Furthermore, we found that the reduction in the transcription of viral immediate early genes was not related to the promoter activities of ICP0. CONCLUSIONS: Therefore, the identification of compound MD as an inhibitor of toxicity induced by HSV-1 highlights its potential use in the development of novel anti-HSV-1 drugs.